Normalization of blood loss in women with heavy menstrual bleeding treated with an oral contraceptive containing estradiol valerate/dienogest - Fraser, Ian S.; Jensen, Jeffrey; Schaefers, Matthias; Mellinger, Uwe; Parke, Susanne; Serrani, Marco (REPRODUCTIVE ENDOCRINOLOGY, 2014)
The study was conducted to assess the efficacy of estradiol valerate/dienogest (E₂V/DNG) administered using an estrogen step-down and progestogen stepup approach in a 28-day regimen in the treatment of heavy menstrual bleeding (HMB) using clinical end points allowing E₂V/DNG to be compared with other available medical therapies. This was a pooled analysis of data from two identically designed randomized, placebo-controlled, multiple center studies conducted in Europe, Australia and North America that assessed the effectiveness of E₂V/DNG in reducing menstrual blood loss (MBL) in women with HMB. Women aged ≥ 18 years with objectively confirmed HMB were randomized to E₂V/DNG (n=220) or placebo (n = 135) for seven treatment cycles. Outcomes analyzed included absolute reduction in MBL from baseline, proportion of women successfully treated (defined as MBL below 80 mL and ≥ 50% reduction in MBL), proportion with MBL below 80 mL and proportion with ≥ 50% reduction in MBL from baseline. At study end, 63.6% and 11.9% of patients were successfully treated with E₂V/DNG and placebo, respectively, with 68.2% and 15.6% of women with MBL below 80 mL, and 70.0% and 17.0% with MBL reduction ≥ 50% (all p<.001). Conclusion: E₂V/DNG is highly effective for the treatment of HMB and is associated with a high rate of treatment success.